Pengaruh Customer Experience dan Brand Image terhadap Word of Mouth Marketing di Ahass Sumber Rejeki Baru Kenjeran Surabaya - Herdito Al Ghifari R.M.; Andry Herawati; Anita Asnawi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The increasing population of motor vehicles in Indonesia compels after-sales service providers to improve marketing tactics based on recommendations to maintain market share. This study aims to analyze and explain the significance of the influence of customer experience and brand image on the effectiveness of Word of Mouth (WOM) marketing among customers of the AHASS Sumber Rejeki Baru Kenjeran workshop in Surabaya. Employing a quantitative approach, data were collected via electronic questionnaires from 160 respondents selected using the Slovin formula. Instrument testing (validity and reliability), multiple linear regression analysis to test hypotheses partially (t-test) and concurrently (F-test), and traditional assumption tests (normality, linearity, heteroscedasticity, and multicollinearity) were among the data analysis techniques used. This study finds the regression equation Y = 0.121 + 0.463X₁ + 0.507X₂ reveal that both customer experience and brand image have a favorable and noteworthy impact on WOM. Empirical findings indicate that brand image is the variable that dominates in triggering customer recommendation behavior, supported by a high coefficient of determination (R-squared) of 83.9%. This study concludes that strengthening the synergy between satisfying service experiences and a robust institutional image is key to expanding customer-based promotional reach within the automotive sector.